EXPLORING THE POTENTIAL BENEFITS AND ETHICAL IMPLICATION OF INTEGRATING ARTIFICIAL INTELLIGENCE INTO TECHNICAL EDUCATION PROGRAMME IN KANO STATE TERTIARY INSTITUTIONS (NAU Journal of Technology and Vocational Education, 2026)
The study explored the potential benefits and ethical implications of integrating artificial intelligence into technical education programme in Kano State tertiary institutions. Two research questions guided the study and two null hypotheses were tested. The study adopted the descriptive survey design. The population of the study comprised 1,266 Technical education students in the five government tertiary institutions in Kano State that run technical education programme. Simple random sampling technique was used to obtain a sample size of 300 from technical education students. A 16-item structured questionnaire was used for the study. Three research experts validated the questionnaire instrument. The reliability of the items instrument was ensured using pilot test method and data obtained were analyzed using Cronbach alpha. The analysis yielded an overall reliability coefficient of 0.92 which was suitable for the study. Mean and standard deviation were used to answer the research questions while Analysis of Variance was used to test the hypotheses at a significance level of 0.05. The findings of the study revealed that AI-empowered systems facilitate personalized-learning, enable adaptive learning and real-time feedbacks on learning progression. However, AI ethical concerns in education were identified to include but not limited to: data privacy and security, algorithmic bias, unfairness, among others. The study concluded that AI-powered personalized and adaptive learning platforms are crucial in education because they analyze individual student data to customize learning paths, materials, and pace, ultimately improving engagement, motivation and academic outcomes. It was recommended that AI technology developers and regulatory bodies should ensure that they engaged in the implementation and enforcement of data privacy regulations to safeguard personal information.
Keywords: Benefits of Artificial Intelligence; Technical Education; Ethical Implication; Education; Nigerian Tertiary Institutions